Penilaian Channel Advertising Dalam Akuisisi Pelanggan Berbasis Penggunaan Media Sosial - Siti Monalisa (UIN Sultan Syarif Kasim Riau, 2020)
Ammar Qurta in an independent business brand that focused as producer of muslim wear. In promotional sector, Ammar Qurta used the social media account such as Facebook and Instagram to provide some informations about their product. However, the owner of this brand stated that way was not effective because of the information that they provide was just based on account relation-bond and not massive. By using CRM’s operational (campaign management), paid advertising is one of the best solution for Ammar Qurta’s promotion. But, the use of paid advertising on social media certainly has a difference in terms of the gain of audience engaged. Therefore, the aim of this study is to measure the level of audience engaged of paid advertising to the two social media that Ammar Qurta uses. This study used the Independent T-test to campare the acquisiton level of audience engaged. Based on the results of the study, the use of paid advertising on Facebook for 31 days has a significant audience engaged to Instagram. So it can be concluded that the use of Facebook advertising is more effective than Instagram Adverting on audience engagement terms of Ammar Qurta’s promotion.